2013
DOI: 10.1017/s1092852912001010
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodinamics of psychotropic drugs: effect of sex

Abstract: Data on the specific effects of sex on pharmacokinetics, as well as tolerability, safety, and efficacy of psychotropic medications are still meager, mainly because only recently sex-related issues have attracted a certain degree of interest within the pharmacological domain. Therefore, with the present study, we aimed to provide a comprehensive review of the literature on this topic, through careful MEDLINE and PubMed searches of the years 1990-2012. Generally, data on pharmacokinetics are more consistent and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 93 publications
4
47
0
2
Order By: Relevance
“…Second, results regarding the different pattern of improvement were not cleared for medication type and dosage and for gender related latency. Indeed, different pharmacokinetic characteristics in men and women may influence plasma levels of psychotropic drugs and, perhaps, their effectiveness as recently confirmed (Meibohm et al, 2002;Marazziti et al, 2013). Finally, it would be interesting to confirm our findings on gender differences at the time of the admission and after a brief hospitalization in other diagnoses.…”
Section: Discussionsupporting
confidence: 70%
“…Second, results regarding the different pattern of improvement were not cleared for medication type and dosage and for gender related latency. Indeed, different pharmacokinetic characteristics in men and women may influence plasma levels of psychotropic drugs and, perhaps, their effectiveness as recently confirmed (Meibohm et al, 2002;Marazziti et al, 2013). Finally, it would be interesting to confirm our findings on gender differences at the time of the admission and after a brief hospitalization in other diagnoses.…”
Section: Discussionsupporting
confidence: 70%
“…There are different factors causing these differences, such as hormonal changes and differences in body weight (29,30). Women present a higher Vd/W than men, due to their highest fat percentage (30).…”
Section: Sex Influence On Pharmacokineticsmentioning
confidence: 99%
“…This difference can somewhat be explained by reduced gastric emptying, lower body weight, reduced volume of distribution and lower hepatic blood flow in females (Gandhi et al 2004). Moreover, higher serum concentrations of venlafaxine in females might also be explained by slower hydroxylation and glucuronidation possibly due to drug metabolizing effects of estrogens and progesterone (Marazziti et al 2013). In the present study, females demonstrated an approximately 24 % increase in dose-adjusted serum concentrations of the venlafaxine active moiety, compared with males (Table 2).…”
Section: Influence Of Age Sex and Bmimentioning
confidence: 99%